Merawat Ciptaan, Meruntuhkan Kuasa: Kritik Teologis terhadap Ekologi Kolonial melalui Spiritualitas Dayak - John Stevie Manongga (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2025)
The global ecological crisis is not merely an environmental issue but reflects a theological rupture in the relationship between humanity, creation, and the power structures that sustain them. This study offers a theological critique of colonial ecologies by exploring the spiritual-ecological practices of the Dayak communities in Kalimantan, particularly the conservation of simpukng and the agrarian ritual of nyelapat taun. It employs a qualitative approach grounded in conceptual-reflective literature analysis, utilizing a postcolonial deconstructive methodology within ecotheology to interpret indigenous practices as theological-hermeneutical fields. The study reinterprets these traditional ecological knowledge (TEK) practices in light of the Christian doctrine of Imago Dei, which has often been framed within anthropocentric paradigms. The findings reveal that Dayak spirituality not only supports biodiversity conservation and ecosystem regeneration but also embodies a relational paradigm between humans and nature, rooted in the community’s spiritual laws. Through this approach, the article argues that caring for creation is not merely an ecological obligation but a theological vocation that requires dismantling exploitative power structures. The integration of local wisdom and Christian theology thus opens a decolonial path toward an ecological future that is holistic, just, and spiritually grounded.